Orbital SCF energies in the double proton transfer of the adenine-thymine base pair - Marañón, Julio (1983)
The double-minimum potential generated by the proton motion involved in the two hydrogen bonds of the adenine-thymine base pair can be accounted for through the orbital-energy spectrum. The results show that the greatest interaction between the molecular orbitals is found when the interprotonic distance of the protons is optimum,i.e. at the top of the barrier of the double-minimum potential. This raises the question of charge transfer electronic transitions as a possibility of modelling the behaviour of the double proton transfer in the excited states of this base pair.